2022
DOI: 10.3390/cryst12050670
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Irradiation Effect of Inverted Metamorphic Triple Junction GaInP/GaAs/InGaAs Solar Cells

Abstract: Inverted metamorphic triple junction (IMM3J) GaInP/GaAs/InGaAs solar cells have the advantages of high efficiency, excellent radiation resistance, lightweight and flexible properties, especially suitable for space application. In this paper, we first fabricate the IMM3J GaInP/GaAs/InGaAs solar cell, which has a short circuit current density of 16.5 mA/cm2, an open circuit voltage of 3141.8 mV, a fill factor of 84.3%, and an efficiency of 32.2%. Then, the IMM3J solar cell is irradiated by 2 MeV protons with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This means that a larger percentage of incident photons can be converted into electrical energy, resulting in greater overall conversion efficiency. [13][14][15][16] In addition, flexible IMM solar cells have the advantages of high efficiency, excellent radiation resistance, lightweight, and flexible properties, making them suitable for various applications.…”
Section: Introductionmentioning
confidence: 99%
“…This means that a larger percentage of incident photons can be converted into electrical energy, resulting in greater overall conversion efficiency. [13][14][15][16] In addition, flexible IMM solar cells have the advantages of high efficiency, excellent radiation resistance, lightweight, and flexible properties, making them suitable for various applications.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the incidence of electrons introduces lattice defects in the cells that act as recombination centers, directly impacting carrier lifetimes. A reviewed report found that radiation damage in solar cells causes a reduction in minority carrier diffusion length and thereby reduces overall conversion efficiency [ 39 , 40 , 41 , 42 , 43 ]. Based on the above reviews, irradiation by high-energy radiation particles degrade the physical properties of irradiated semiconductor materials.…”
Section: Introductionmentioning
confidence: 99%